ON THE USE OF REMOTE SENSING SATELLITE IMAGERY AND THEMATIC MAPPING FOR CULTURAL PURPOSES (PANGEEA, 2025)
Preservation and revitalization of our cultural and natural heritage has a vital role not only in understanding our past, but also in our future development as humans. This paper aims to present the current directions and the use of remote sensing satellite imagery in identifying different terrain forms, routes, objectives and analyzing their evolution over time both for cultural and environmental purposes. A case study was carried out to investigate the contribution of processing remote sensing images to the research and detection of an important former commercial connection between Europe and Asia, the old Silk Road. The analysis of the multi-spectral remote sensing data was performed with the help of innovative programs developed by PIESAT Information Technology Co Ltd. These softwares use an object-oriented analyzing method and have made a qualitative leap in image information extraction. The actuality of the paper is given by the fact that preserving cultural heritage and historical sites represents an important issue that must be taken into account when sustainable development projects are required for environmental policies.
Keywords: sustainable development; cultural heritage; remote sensing; environmental policies